Pentium 4: Old School yet Modern in Engineering - Heena, Sayed; Shaikh, Salman; shaikh, Taha; Rashid, Abdul; Khatri, Nadim (International Journal of Computer Sciences and Engineering, 2019)
In the last few years, technology, especially microprocessors, have had huge advancements and they are expected to have even more in future therefore with this rapidly growing phase of technology, is it still possible to use microprocessors that were considered to be the most advance, at the time, not to long ago? The project aims to analyze the working and applications of the pentium 4 microprocessor that was released in November 20,2000. And this analysis in turn will provides an in-depth examination of the features and function of Pentium 4 microprocessor.